The Concept Of Moderate Islam: Monarchy Tools For Legitimacy In United Arab Emirates (UAE) - Binti Syed Mustaffa, Sharifah Umairah (UI Scholars Hub, 2025)
The conceptualisation of religion from the perspective of power entails the state’s effort to utilise religious resources and symbols as proxy tools. In the aftermath of the Arab Spring in 2010, the state realised the threat of opposition from the independent Islamic movement to the survivability of the monarchical and autocratic regime. Hence, this study identifies the act of the UAE government in confronting the Islamic movement and its role in controlling a religious discourse based on the concept of Moderate Islam, employing a top-down approach to form a distinct religious identity that differs from that of rival countries. Qualitative analysis through the collection of information and reference materials aims to identify the history and factors of the development of Moderate Islam in the UAE. The researcher's initial hypothesis asserts that there are three forms of the government's approach in establishing the concept of Islam in the UAE, namely coercing Islamic group, control over religious institutions and promoting the narrative of moderation through various platforms and endorsing two contradicted sects of Neo-traditionalists and anti-traditionalists which have the similarities in terms of separation of religious interference in politic. Thus, this study will examine the concept of Moderate Islam in the UAE and its implications for the legitimacy of the monarchy.